Life parameters of the synovivenic parasitoid Tamarixia triozea (Hymenoptera. Eulophidae) - Morales A., Sinue Isabel; Martínez, Ana Mabel; Figueroa, José Isaac; Espino H., Alma Mirella; Chavarrieta Y., Juan Manuel; Ortíz R., Ruy; Rodríguez E., Christian Luis; Pineda, Samuel (Revista Colombiana de Entomología, 2013)
Parasitism (proportion of parasitized nymphs) and host-feeding (proportion of consumed nymphs) of Tamarixia triozae females of different ages was evaluated on N3-N4-N5 instars of Bactericera cockerelli on tomato (Solanum lycopersicum) leaflets, together with the sex ratio and longevity of the progeny (F1 generation). Irrespective of the female age, the parasitism rate was not significantly different on N3 and N5 instars, but the oldest females (10 and 12.5 d-old) parasitized significantly more N4 than the youngest ones. Within a female age, the parasitism of T. triozae increased with the age of the nymph when they were young (3-4.5 and 6 d-old) and did not change when they were older (7.5 to 12.5 d-old). Host-feeding was independent of the parasitoid female age (maximum of 28 ± 4 for N3 and 7.5 d-old females) and was lower on older nymphal stages of the host. A significantly higher number of males were only detected in the offspring of 12.5 d-old females that parasitized N3 nymphs. Female longevity was longer, but not statistically significant differences were obtained. In host-feeding preference experiments with three nymphal stages of B. cockerelli (N3-N4-N5) and leaflets of two host plants [tomato and chili pepper (Capsicum annuum)], neither nymphal instars nor plant species had a significant effect on the parasitism rate. However, T. triozae female host-feeding was inversely related to the nymphal instar offered. In conclusion, the combination of T. triozae female parasitism and hostfeeding on B. cockerelli nymphs may significantly affect the population dynamics of this pest.